Pengaruh LDR, BOPO, dan NPL terhadap ROA pada BUSN Devisa Terdaftar di BEI Periode 2014-2018 - Yeni Siti Halimatus Sadi’yah; Muhamad Umar Mai; Rosma Pakpahan (Indonesian Journal of Economics and Management, 2021)
This research aims to analyse the influence of Loan To Deposit Ratio, Operational Efficiency Ratio and Non Performing Loan to Return On Asset at national private Bank of foreign exchange listed on Indonesia Stock Exchange period 2014-2018. The population of this research is the national private Bank of foreign exchange listed on the Indonesia Stock Exchange period 2014-2018, a research sample of 23 bank companies using the purposive sampling method. The analysis used to determine the influence of Loan To Deposit Ratio (LDR), Operational Efficiency Ratio (OER) and Non Performing Loan (NPL) to Return On Asset (ROA) is a descriptive and quantitative analysis with using the help of software Eviews 10. The results indicate that simultaneously LDR, OER, and NPL variables have significant effect on ROA. The LDR has a significant and positive impact on ROA, OER and NPL have significantly negative and significant impact on ROA